1998
DOI: 10.1111/j.1365-2044.1998.00272.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemodilution tolerance in patients with mitral regurgitation

Abstract: SummaryHaemodynamic parameters and oxygen consumption were determined in 20 patients with mitral regurgitation before and after a 12 ml.kg ¹1 isovolaemic exchange of blood for 6% hydroxyethyl starch. During haemodilution, mean (SEM) haemoglobin concentration decreased from 13.0 (0.4) to 10.3 (0.4) The avoidance of blood transfusion is an important issue in the care of surgical patients. Haemodilution and acceptance of minimal haemoglobin values in the peri-operative period are becoming increasingly advocated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 11 publications
1
5
0
3
Order By: Relevance
“…Narkotisierte Patienten mit Mitralinsuffizienz und Vorhofflimmern tolerierten eine Hämodilution auf Hb 10,3±0,4 g/dl (6,39±0,25 mmol/l) problemlos [98]. Bei narkotisierten Patienten mit hochgradiger Aortenstenose (KÖF 0,6±0,1 cm 2 ) waren die kardialen Kompensationsmechanismen der Anämie bei Hb 9,1±0,9 g/dl (5,65±0,56 mmol/l) erschöpft [58].…”
Section: Myokardperfusion Und -Funktionunclassified
“…Narkotisierte Patienten mit Mitralinsuffizienz und Vorhofflimmern tolerierten eine Hämodilution auf Hb 10,3±0,4 g/dl (6,39±0,25 mmol/l) problemlos [98]. Bei narkotisierten Patienten mit hochgradiger Aortenstenose (KÖF 0,6±0,1 cm 2 ) waren die kardialen Kompensationsmechanismen der Anämie bei Hb 9,1±0,9 g/dl (5,65±0,56 mmol/l) erschöpft [58].…”
Section: Myokardperfusion Und -Funktionunclassified
“…Patients with mitral valve insufficiency showed a good tolerance to hemodilution to hemoglobin levels of 10 g/dL, even in case of the loss of atrial contraction due to atrial fibrillation (42).…”
Section: Heartmentioning
confidence: 99%
“…13 Aortic stenosis and heart failure can interfere with anemia compensatory mechanisms as well, but patients with mitral valve insufficiency usually tolerate anemia well. 14 It has been suggested that the main compensatory mechanism in response to normovolemic hemodilution in elderly patients is increased oxygen extraction and raised arterial oxygen tension as opposed to solely increased CO. Thus, decreasing Hb can reduce DO 2 to organs significantly.…”
Section: S38mentioning
confidence: 99%